The Pacto de Sangre in the late nineteenth-century nationalist emplotment of Philippine history - Aguilar, Filomeno V., Jr. (Quezon City Ateneo de Manila University, 2010)
"The Pacto de Sangre (Blood Compact), despite its crucial significance in Filipino conceptions of history, is seldom interrogated in Philippine historiography. The event that happened in Bohol in 1565, involving Sikatuna and Lezpi, was narrativized in the late nineteenth century and became integral to the nationalist emplotment of the past. However, the two principal narrative strands of Marcelo del Pilar and Andres Bonifacio differed owing to divergent political projects. This article revisits the making of a founding myth of Filipino nationhood in light of scholarship on ancient blood oaths and the historical account of the encounter of Sikatuna and Legazpi."
Vol. 58, nos. 1-2 (June 2010)
Keywords: Nationalism -- Philippines; Philippine history